2014
DOI: 10.1159/000358725
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Benefit of Complementary Therapy Use among People with Diabetes and Cardiovascular Disease

Abstract: Background: Little is known about why and how people with type 2 diabetes and cardiovascular disease (CVD) use CAM, or of the perceived benefits of CAM use. The CAMELOT study explored care-seeking, self-management, costs, barriers and benefits of CAM use among this population. We report here on CAM used for treatment of diabetes and CVD, and non-clinical outcomes of CAM use. Methods: Data were collected in 2009-2010 via in-depth interviews (n = 69) and a self-report questionnaire (n = 2,915) among people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
10
0
2
Order By: Relevance
“…Female patients are linked with more use of nutraceutical products than male patients in this study. Many studies have also suggested that females have increased the use of CAM compared to males [ 5 , 9 , 11 , 19 23 ]. Gender remains statistically significant after multiple logistic regression was conducted to adjust for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…Female patients are linked with more use of nutraceutical products than male patients in this study. Many studies have also suggested that females have increased the use of CAM compared to males [ 5 , 9 , 11 , 19 23 ]. Gender remains statistically significant after multiple logistic regression was conducted to adjust for confounders.…”
Section: Discussionmentioning
confidence: 99%
“…herbs, vitamins, minerals or other nutritional supplements). Types of CAMs used, their frequency and reasons for use varied (see elsewhere for details of CAM products and practitioners used): 77.3% of CAM practitioner users and 57.6% of CAM product users (7.4% missing) used CAM to treat chronic conditions – with 41.3 and 33.1%, respectively, using CAM for the treatment or management of their diabetes or CVD. Half (50.7%) used CAM to prevent illness or improve health and well‐being, 14.4% to treat acute or short term illness and 13.6% for weight loss (respondents were able to choose one or more reasons).…”
Section: Resultsmentioning
confidence: 99%
“…Consulting a variety of different CAM practitioners, over a long period of time, was not unusual. Practitioner provided CAM therapies most commonly reported for diabetes or CVD treatment were manipulative and massage‐based therapies, naturopathy, acupuncture, Chinese medicine, Reiki, kinesiology, western herbalism and homoeopathy …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…seeking more personal person-centred care, to support holistic healthcare needs, or to manage comorbidities. 48,49 Therefore, the scoping review will also seek to identify other common or important reasons and problems for T&CM use by this patient group that are not listed in Table 2.…”
Section: Patient/problem/populationmentioning
confidence: 99%